A fluorinated vanadium phosphate salt magnesium battery positive electrode material and a preparation method and application thereof
Patent Information
- Application Number
- CN202411164034.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-08-23
AI Technical Summary
所得正极材料可以获得较好的循环稳定性,但仅有62.6mAh g-1的放电比容量且材料结晶性较差,在实际应用中依然存在一定问题
[0035]1)本发明所提供的氟化磷酸钒盐镁电池正极材料,具有可脱嵌的活性镁离子和快离子传输通道,电化学性能优异。其中Mg元素不仅可以提供活性脱嵌离子,提升材料放电比容量;Na元素可以有效稳定材料框架结构,进而提升材料循环稳定性;F元素则能有效提升反应电位,进而提高工作电压。而该正极材料同时含有Mg、Na和F三种元素时,该Mg、Na、F三种元素具有较好的协同作用,三者共同作用可有效提升磷酸盐正极的比容量、循环稳定性和工作电压。且由该氟化磷酸钒盐镁电池正极材料组装得到的镁电池,工作电压为2.3V以上,远远高于其他类型的镁电池正极材料(硫化物:~1.0V;氧化物:~1.5V),首周可逆比容量高达120mAh/g,可稳定循环100周以上;
Smart Images

Figure CN119133439B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of energy storage materials technology, specifically relating to a fluorinated vanadium phosphate magnesium battery cathode material, its preparation method, and its application. Background Technology
[0002] Magnesium-ion batteries benefit from good air stability, a smaller ionic radius (0.072 nm), a lower reduction potential (-2.356 V relative to a standard hydrogen electrode), and a higher volumetric capacity (3833 mAh / cm³). 3 Compared to other types of lithium-ion battery technology, magnesium exhibits greater application potential. Furthermore, magnesium reserves in the Earth's crust (2.3%) are 1045 times greater than lithium reserves (0.0022%), resulting in abundant magnesium resources and lower production costs. Moreover, metallic magnesium is relatively stable in air and does not readily grow magnesium dendrites, making the development of high-performance magnesium-ion battery technology for large-scale energy storage extremely attractive.
[0003] However, the high charge density and strong solvation of magnesium ions result in reversible insertion / extraction in the cathode material and slow ion diffusion at the solid-liquid interface, severely affecting the electrochemical performance of magnesium-ion batteries. Phosphate-based cathode materials exhibit higher ionic conductivity (approximately 10⁻⁶). -3 S / cm) and a structurally stable three-dimensional open framework, for Mg 2+ Ion intercalation provides sufficient lattice gaps, offering advantages such as high operating voltage and structural stability. However, the operating voltage is very limited, affecting the overall energy density of magnesium-ion batteries.
[0004] CN202310598433.0 discloses a phosphate cathode material for rechargeable magnesium batteries, wherein the phosphate Mg x M 3-x The preparation method of (PO4)2 can effectively combine the advantages of traditional solid-state methods, sol-gel methods, and hydrothermal methods to obtain a uniform phosphate precursor, with a capacity of up to 141.8 mAh g in three-electrode testing. -1 However, its operating voltage is not high, and its capacity retention rate is less than 80%.
[0005] CN202311786628.4 discloses a method for preparing silicate cathode material MgFeSiO4 and its applications. A simple and efficient electrojoule heating method enables rapid preparation of the target product. The resulting cathode material exhibits good cycle stability, but its discharge specific capacity is only 62.6 mAh g⁻¹, and the material has poor crystallinity, which still presents certain challenges for practical applications.
[0006] Breakthroughs are urgently needed in the development of polyanionic cathode materials with high operating voltage and high discharge capacity. Summary of the Invention
[0007] This invention aims to at least partially solve one of the technical problems in related technologies. Therefore, the main objective of this invention is to provide a magnesium vanadium fluoride phosphate battery cathode material with high energy density and good cycle stability, and a method for preparing the same.
[0008] The objective of this invention is achieved through the following technical solution:
[0009] A fluorinated vanadium phosphate magnesium battery cathode material, wherein the chemical composition of the fluorinated vanadium phosphate magnesium battery cathode material is: Mg a Na b V 2-x M x (PO4) 3-y F y M is one or more of Fe, Ti, Cr, Ni, Cu, Mn, Co, and Nb, 0 < a ≤ 1.5, 0 < b ≤ 3, 0 < x ≤ 1.3, and 0 < y ≤ 3.
[0010] Furthermore, the particle size of the fluorinated vanadium phosphate magnesium battery cathode material is 0.1 μm to 20 μm, and its morphology is one of nanoparticles, microspheres, or microbulb structures.
[0011] The present invention also provides a method for preparing a magnesium vanadium fluoride battery cathode material, comprising the following steps:
[0012] 1) Mix the raw materials, including vanadium source, transition metal M source, magnesium source, sodium source and fluorine source, evenly and carry out a chemical reaction;
[0013] 2) The product after the reaction is completed is washed and dried to obtain the fluorinated vanadium phosphate magnesium battery cathode material.
[0014] In some specific embodiments, the vanadium source includes any one or a combination of at least two of trivalent vanadium sources, tetravalent vanadium sources, and pentavalent vanadium sources;
[0015] The transition metal M source is one or more of the following: iron source, titanium source, chromium source, nickel source, copper source, and cobalt source;
[0016] The iron source is any one or a combination of at least two of the following: ferrous fluoride, ferrous chloride, ferrous bromide, ferrous nitrate, ferrous sulfate, ferrous carbonate, ferrous oxalate, ferrous acetate, ferrous hydroxide, ferrous oxide, ferrous sulfide, ferrous acetylacetone, ferric fluoride, ferric chloride, ferric bromide, ferric nitrate, ferric sulfate, ferric carbonate, ferric oxalate, ferric acetate, ferric hydroxide, ferric oxide, ferric tetroxide, or ferric acetylacetone.
[0017] The titanium source is any one or a combination of at least two of the following: titanium chloride, titanium bromide, titanium sulfate, titanium nitrate, titanium oxalate, titanium formate, titanium acetate, titanium dioxide, titanium acetylacetone, and tetrabutyl titanate.
[0018] The chromium source includes any one or a combination of at least two of the following: chromium trichloride, chromium tribromide, chromium nitrate, chromium sulfate, chromium oxalate, chromium formate, chromium acetate, chromium chromate, chromium lactate, basic chromium sulfate, chromium perchlorate, chromium trioxide, chromium hydroxide, chromium acetylacetone, sodium chromate, and sodium dichromate.
[0019] The nickel source is any one or a combination of at least two of nickel fluoride, nickel chloride, nickel bromide, nickel nitrate, nickel sulfate, nickel carbonate, nickel oxalate, nickel acetate, nickel hydroxide, nickel oxide, nickel sulfide, and nickel acetylacetonate.
[0020] The copper source is any one or a combination of at least two of the following: copper fluoride, copper chloride, copper bromide, copper nitrate, copper sulfate, copper carbonate, copper oxalate, copper acetate, basic copper carbonate, copper hydroxide, copper oxide, copper sulfide, and copper acetylacetonate.
[0021] The manganese source is any one or a combination of at least two of the following: manganese fluoride, manganese chloride, manganese bromide, manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese acetate, manganese hydroxide, manganese oxide, manganese sulfide, manganese acetylacetonate, manganese trifluoride, manganese trichloride, manganese tribromide, manganese nitrate, manganese sulfate, manganese carbonate, manganese oxalate, manganese acetate, manganese hydroxide, manganese trioxide, manganese dioxide, and manganese acetylacetonate.
[0022] The cobalt source is any one or a combination of at least two of cobalt acetate, cobalt oxide, cobalt carbonate, cobalt nitrate, and cobalt chloride.
[0023] Furthermore, the vanadium source includes any one or a combination of at least two of the following: vanadium trichloride, vanadium tribromide, vanadium trioxide, vanadium acetylacetonate, vanadium dichloride, vanadium oxysulfate, vanadium oxalate, vanadium dioxide, vanadium acetylacetonate, vanadium trichloride, sodium vanadate, sodium metavanadate, ammonium metavanadate, vanadium pentoxide, vanadium-titanium magnetite, or metallurgical vanadium slag.
[0024] In some specific embodiments, when the vanadium source and the transition metal source are in a high oxidation state, the reaction raw materials also include a reducing agent; the reducing agent is any one or more of ascorbic acid, oxalic acid, citric acid, charcoal, and hydroxylamine hydrochloride.
[0025] In some specific embodiments, the molar ratio of vanadium, transition metal M, magnesium, sodium, phosphorus and fluorine in the fluorinated vanadium phosphate magnesium battery cathode material is 1:(0~1):(1~5):(1~5):(1~10):(0.5~8).
[0026] In some specific embodiments, the magnesium source includes any one or a combination of at least two of magnesium phosphate, magnesium hydrogen phosphate, magnesium fluoride, magnesium acetate, magnesium vanadate, magnesium bromide, magnesium chloride, magnesium carbonate, or magnesium perchlorate.
[0027] The sodium source includes any one or a combination of at least two of the following: sodium phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium fluoride, sodium acetate, sodium orthovanadate, sodium metavanadate, sodium bromide, sodium chloride, or sodium carbonate.
[0028] The fluorine source includes any one or a combination of at least two of sodium fluoride, ammonium fluoride, potassium fluoride, magnesium fluoride, calcium fluoride, aluminum fluoride, or lithium fluoride.
[0029] In some specific embodiments, the chemical reaction is one of a high-energy ball milling reaction, a room-temperature coprecipitation reaction, or a hydrothermal reaction.
[0030] When high-energy ball milling is used, the material has a nanoparticle structure with a particle size between 100-200 nm; when room temperature coprecipitation reaction is used, the product exhibits a micron-sized spherical structure with a particle size between 10-15 μm; when hydrothermal reaction is used, the product exhibits a micron-sized blocky structure with a particle size between 5-10 μm.
[0031] In some specific embodiments, the washing and drying processes specifically involve: the washing medium includes water and / or an organic solvent, and the washing is performed 4 to 6 times; the drying temperature is 50 to 70°C, and the drying time is 3 to 6 hours.
[0032] Furthermore, the organic solvent is one or more of ethanol, acetone, or N-methylpyrrolidone.
[0033] The purpose of this invention is to also provide the application of this fluorinated vanadium phosphate magnesium battery cathode material in magnesium ion cathode materials.
[0034] Compared with the prior art, the present invention has at least the following advantages:
[0035] 1) The fluorinated vanadium phosphate magnesium battery cathode material provided by this invention possesses active magnesium ions capable of insertion and extraction, as well as fast ion transport channels, exhibiting excellent electrochemical performance. Mg not only provides active insertion and extraction ions, enhancing the material's discharge specific capacity; Na effectively stabilizes the material's framework structure, thereby improving cycle stability; and F effectively increases the reaction potential, thus raising the operating voltage. When this cathode material contains Mg, Na, and F simultaneously, these three elements exhibit a good synergistic effect, effectively improving the specific capacity, cycle stability, and operating voltage of the phosphate cathode. Furthermore, the magnesium battery assembled from this fluorinated vanadium phosphate magnesium battery cathode material has an operating voltage exceeding 2.3V, significantly higher than other types of magnesium battery cathode materials (sulfides: ~1.0V; oxides: ~1.5V), a first-cycle reversible specific capacity as high as 120mAh / g, and can stably cycle for over 100 cycles.
[0036] 2) The method for preparing the vanadium fluoride magnesium phosphate battery cathode material provided by the present invention uses raw materials that can be effectively synthesized under low energy consumption conditions, and the synthesis process is simple and suitable for large-scale application. Attached Figure Description
[0037] To more clearly illustrate the specific embodiments of the present invention, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.
[0038] Figure 1 The XRD diffraction pattern of the magnesium vanadium fluoride battery cathode material provided in Example 1;
[0039] Figure 2 SEM image of the magnesium vanadium fluoride battery cathode material provided in Example 1;
[0040] Figure 3 The first-cycle charge-discharge curve of the battery prepared from the fluorinated vanadium phosphate magnesium battery cathode material provided in Example 1 at a rate of 0.5C.
[0041] Figure 4 SEM image of the magnesium vanadium fluoride battery cathode material provided in Example 2;
[0042] Figure 5 The image is a SEM image of the magnesium fluoride vanadium phosphate battery cathode material provided in Example 3. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The following embodiments are merely descriptive and not limiting, and should not be construed as limiting the scope of protection of the present invention.
[0044] When a quantity, concentration, or other value or parameter is described as a range, preferred range, or preferred upper and lower limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper or preferred values with any lower or preferred values, regardless of whether the range is specifically disclosed. Unless otherwise stated, the numerical range values listed herein include the endpoints of the range and all integers and fractions within that range.
[0045] Unless otherwise stated, all percentages, parts, ratios, etc. in this document are by weight.
[0046] The materials, methods, and embodiments described herein are exemplary and should not be construed as limiting unless otherwise stated.
[0047] Example 1
[0048] This embodiment provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0049] (1) Dissolve 1 mmol magnesium acetate, 1 mmol sodium fluoride, 2 mmol ammonium metavanadate, 2 mmol sodium dihydrogen phosphate, and 3 mmol hydroxylamine hydrochloride in 40 mol deionized water. After complete dissolution, place the solution in a polytetrafluoroethylene (PTFE) liner. Place the PTFE liner in a hydrothermal reactor and heat it to 120°C at a rate of 5°C / min. Maintain this temperature for 10 h and then cool it to room temperature with the furnace to obtain a suspension containing the target product MgNa(VOPO4)2F.
[0050] (2) The suspension described in (1) is washed three times with deionized water and anhydrous ethanol, and then dried at 60°C for 5 hours to obtain the MgNa(VOPO4)2F magnesium ion battery cathode material.
[0051] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0052] The prepared MgNa(VOPO4)2F powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) at a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, and assembled into CR2032 coin cells.
[0053] from Figure 1 The XRD results show that the magnesium-ion battery cathode material provided in Example 1 is a pure phase. Figure 2The SEM results show that the magnesium-ion battery cathode material provided in Example 1 has a micron-sized bulk structure with a particle size of about 15 μm.
[0054] from Figure 3 It can be seen that within the voltage window of 0.5–3.2V, the discharge specific capacity at a 0.5C rate is 99 mAhg. -1 The operating voltage is 2.3V; the capacity retention rate is 81% after 100 cycles.
[0055] Example 2
[0056] This embodiment provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0057] (1) Place 0.9 mmol magnesium oxalate, 1.5 mmol sodium acetate, 1 mmol sodium metavanadate, 1 mmol manganese acetate, 2 mmol concentrated phosphoric acid, and 3 mmol magnesium fluoride into a ball mill jar. Prepare the ball mill beads according to a reactant-to-milling-bead mass ratio of 1:20. React in a three-dimensional ball mill for 5 h to obtain the target product Mg. 0.9 Na 1.5 A mixture of VMn(PO4)2F3;
[0058] (2) Wash the mixture described in (1) five times with deionized water, then dry it at 70°C for 6 hours to obtain Mg. 0.9 Na 1.5 VMn(PO4)2F3 is a magnesium-ion battery cathode material.
[0059] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0060] The prepared Mg 0.9 Na 1.5 VMn(PO4)2F3 powder was mixed with conductive carbon and polytetrafluoroethylene (PTFE) binder at a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0061] from Figure 4 The SEM results show that the magnesium-ion battery cathode material provided in Example 2 has a nanoparticle structure with a particle size of about 100 nm.
[0062] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 108 mAh g. -1 The operating voltage is 2.5V, and the capacity retention rate is 85% after 100 cycles. Specific performance details are shown in Table 1.
[0063] Example 3
[0064] This embodiment provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0065] (1) Take 0.6 mmol magnesium oxalate, 1.8 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol ferric acetate, 0.5 mmol manganese acetate, 2 mmol ammonium dihydrogen phosphate and 3 mmol ammonium fluoride and dissolve them in a 60 ml mixture of acetone and water in a volume ratio of 1:2. After dissolving completely, place the mixture in a beaker and let it stand for 24 h to obtain a suspension containing the target product.
[0066] (2) The suspension described in (1) is washed four times alternately with water and acetone, and then dried at 50°C for 4 hours to obtain Mg. 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 is a magnesium-ion battery cathode material.
[0067] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0068] The prepared Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0069] from Figure 5 The SEM results show that the magnesium-ion battery cathode material provided in Example 3 has a micron-sized spherical structure with a particle size of about 20 μm.
[0070] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 120 mAh g. -1 The operating voltage is 2.4V, and the capacity retention rate is 82% after 100 cycles. Specific performance details are shown in Table 1.
[0071] Comparative Example 1
[0072] This comparative example provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0073] (1) Take 3 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol ferric acetate, 0.5 mmol manganese acetate, 2 mmol ammonium dihydrogen phosphate and 3 mmol ammonium fluoride and place them in a mixed solution of 60 ml acetone and water in a volume ratio of 1:2. After dissolving completely, place the solution in a beaker and let it stand for 24 h to obtain a suspension containing the target product.
[0074] (2) Wash the suspension described in (1) with water and acetone alternately four times, then dry it at 50°C for 4 hours to obtain Na3V. 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 is a magnesium-ion battery cathode material.
[0075] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0076] Prepared Na3V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0077] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 85 mAh g. -1 The operating voltage is 2.2V, and the capacity retention rate is 52% after 100 cycles. See Table 1 for specific performance details.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0080] (1) Take 0.6 mmol magnesium acetate, 1.8 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol iron acetate, 0.5 mmol manganese acetate and 3 mmol ammonium dihydrogen phosphate and place them in a mixed solution of 60 ml acetone and water with a volume ratio of 1:2. After dissolving completely, place the solution in a beaker and let it stand for 20 h to obtain a suspension containing the target product.
[0081] (2) The suspension described in (1) is washed alternately with water and ethanol 6 times, and then dried at 60°C for 5 hours to obtain Mg. 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO4)3 magnesium ion battery cathode material.
[0082] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0083] The prepared Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO4)3 powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0084] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 90 mAh g. -1 The operating voltage is 1.6V, and the capacity retention rate is 56% after 100 cycles. See Table 1 for specific performance details.
[0085] Comparative Example 3
[0086] This comparative example provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0087] (1) Take 1.5 mmol magnesium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol iron acetate, 0.5 mmol manganese acetate, 2 mmol ammonium dihydrogen phosphate and 3 mmol ammonium fluoride and place them in a mixed solution of 60 ml acetone and water in a volume ratio of 1:2. After dissolving completely, place the solution in a beaker and let it stand for 20 h to obtain a suspension containing the target product.
[0088] (2) The suspension described in (1) is washed alternately with water and ethanol 6 times, and then dried at 60°C for 5 hours to obtain Mg. 1.5 V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 is a magnesium-ion battery cathode material.
[0089] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0090] The prepared Mg 1.5 V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0091] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 95 mAh g. -1 The operating voltage is 2.1V, and the capacity retention rate is 31% after 100 cycles. See Table 1 for specific performance details.
[0092] Comparative Example 4
[0093] This comparative example provides a method for preparing a magnesium vanadium fluoride battery cathode material, which includes the following steps:
[0094] (1) Take 0.6 mmol magnesium acetate, 1.8 mmol sodium acetate, 0.5 mmol vanadium acetylacetonate, 1.0 mmol ferric acetate, 0.5 mmol manganese acetate, 2 mmol ammonium dihydrogen phosphate and 3 mmol ammonium fluoride and place them in a mixed solution of 60 ml acetone and water in a volume ratio of 1:2. After dissolving completely, place the solution in a beaker and let it stand for 20 h to obtain a suspension containing the target product.
[0095] (2) The suspension described in (1) is washed alternately with water and ethanol 6 times, and then dried at 60°C for 5 hours to obtain Mg. 0.6 Na 1.8 V 0.5 FeMn 0.5 (PO4)2F3 is a magnesium-ion battery cathode material.
[0096] This application tests the electrochemical performance of the magnesium fluoride vanadium phosphate battery cathode material prepared in this embodiment, specifically as follows:
[0097] The prepared Mg 0.6 Na 1.8 V 0.5 FeMn 0.5 (PO4)2F3 powder was mixed with conductive carbon and binder polytetrafluoroethylene (PTFE) in a mass ratio of 8:1:1, and electrode sheets were prepared by coating or dry method. The magnesium-ion battery was assembled in a glove box under Ar atmosphere, using magnesium metal as the negative electrode sheet, and bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in dimethyl glycol ether (DME) as the electrolyte, to form a CR2032 coin cell.
[0098] Electrochemical performance was tested within a voltage window of 0.5–3.2 V at a rate of 0.5C. The first-cycle discharge specific capacity was 98 mAh g. -1 The operating voltage is 2.0V, and the capacity retention rate is 57% after 100 cycles. See Table 1 for specific performance details.
[0099] Table 1. Electrochemical performance of magnesium vanadium fluoride battery cathode materials in each embodiment and comparative example.
[0100]
[0101] According to the experimental results in Table 1:
[0102] The data results from Examples 1-3 show that the introduction of different transition metals, the element ratios, and the differences in preparation methods can lead to different working voltages and capacities in the materials.
[0103] The data from Example 3 and Comparative Example 1 show that the absence of magnesium in the target cathode has little impact on the first-cycle discharge capacity, but it will lead to a rapid decline in battery cycle performance.
[0104] The data from Example 3 and Comparative Example 2 show that the absence of fluorine in the target cathode material leads to lower working voltage and capacity, and extremely poor cycle retention of the battery.
[0105] The data from Example 3 and Comparative Example 3 show that the absence of sodium in the target cathode leads to a significant reduction in the material's cycle performance.
[0106] The data from Example 3 and Comparative Example 4 show that a low proportion of M element (Fe+V) in the target cathode will lead to a decrease in the material's cycle stability. That is, exceeding the x range will cause a decrease in the material's structural stability, which is not conducive to the performance of electrochemical properties.
[0107] The data from Example 3 and Comparative Examples 1, 2, 3, and 4 show that Mg, Na, and F have a good synergistic effect, and their combined action can effectively improve the specific capacity, cycle stability, and operating voltage of the phosphate cathode.
[0108] In summary, the magnesium-ion battery cathode material composition provided by this invention has excellent operating voltage and charge / discharge capacity, with an operating voltage of up to 2.5V, and high battery stability, maintaining a capacity retention rate of over 80% after 100 cycles at 0.5C.
[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.
Claims
1. A magnesium-ion battery, characterized in that, It includes a magnesium vanadium fluoride battery cathode material, which is prepared by the following method, including the following steps: (1) Take 0.6 mmol magnesium oxalate, 1.8 mmol sodium acetate, 0.8 mmol vanadium acetylacetonate, 0.7 mmol ferric acetate, 0.5 mmol manganese acetate, 2 mmol ammonium dihydrogen phosphate, and 3 mmol ammonium fluoride and place them in a 60 ml mixture of acetone and water at a volume ratio of 1:
2. After dissolving completely, place the mixture in a beaker and let it stand for 24 h to obtain a suspension containing the target product. (2) The suspension described in (1) is washed and dried to obtain Mg 0.6 Na 1.8 V 0.8 Fe 0.7 Mn 0.5 (PO4)2F3 is the positive electrode material for magnesium-ion batteries; and the electrolyte of the magnesium-ion battery is a mixture of bis(trifluoromethanesulfonyl)imide magnesium, aluminum chloride, magnesium chloride, and sodium bis(trifluoromethanesulfonyl)imide dissolved in ethylene glycol dimethyl ether.
2. The magnesium-ion battery according to claim 1, characterized in that, The cathode material of the fluorinated vanadium phosphate magnesium battery has a particle size of 20 μm and a micron-sized spherical structure.
3. The magnesium-ion battery according to claim 2, characterized in that, The washing and drying processes are as follows: the washing medium includes water and acetone, and the washing is performed 4 times; the drying temperature is 50°C, and the drying time is 4 hours.
Citation Information
Patent Citations
Phosphate positive electrode material Mg2M3-x (PO4) 2 (at) C of rechargeable magnesium battery and preparation method and application of phosphate positive electrode material Mg2M3-x (PO4) 2 (at) C
CN116666584A
Preparation method and application of silicate positive electrode material MgFeSiO4
CN117776192A
Carbon-coated magnesium ion-doped modified sodium vanadium fluorophosphate positive electrode material and preparation method thereof
CN115719806A